2000
DOI: 10.1051/lait:2000143
|View full text |Cite
|
Sign up to set email alerts
|

Évaluation du BactoScan FC pour la numération des bactéries du lait cru

Abstract: -Evaluation of BactoScan FC for the enumeration of bacteria in raw milk. The evaluation of BactoScan FC for routine enumeration of bacteria in raw milk was carried out according to the model proposed by the International Dairy Federation. The linearity of response of BactoScan FC was verified between 6 000 and 27 000 000 pulses . mL -1 without reaching the limits of detection which have not been determined. The transmission error was estimated at 0.09% and the repeatability at 0.084 log 10 CFU . mL -1 for a 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
11

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(31 citation statements)
references
References 2 publications
3
17
0
11
Order By: Relevance
“…The obtained s Rl was somewhat better for raw cow's milk than for raw sheep's milk. Still, it was in the same order of magnitude as s r or s R presented in other studies [4,11,17] and it was within desired limits [14]. The only exception was the interval between 10 IBC·µL -1 and 50 IBC·µL -1 for raw sheep's milk, but only a small data set was appraised here.…”
Section: Methods Describing Criteriasupporting
confidence: 65%
See 4 more Smart Citations
“…The obtained s Rl was somewhat better for raw cow's milk than for raw sheep's milk. Still, it was in the same order of magnitude as s r or s R presented in other studies [4,11,17] and it was within desired limits [14]. The only exception was the interval between 10 IBC·µL -1 and 50 IBC·µL -1 for raw sheep's milk, but only a small data set was appraised here.…”
Section: Methods Describing Criteriasupporting
confidence: 65%
“…Upon routine testing it was confirmed that within-laboratory reproducibility of BSC-FC depends on IBC counts [4,11,17], no matter which milk was analysed (Tab. I).…”
Section: Methods Describing Criteriamentioning
confidence: 99%
See 3 more Smart Citations